2006
DOI: 10.1097/01.gim.0000250501.59830.ff
|View full text |Cite
|
Sign up to set email alerts
|

A focus group study of consumer attitudes toward genetic testing and newborn screening for deafness

Abstract: Purpose: Progress in identifying genes for deafness together with implementation of universal audiologic screening of newborns has provided the opportunity for more widespread use of molecular tests to detect genetic forms of hearing loss. Efforts to assess consumer attitudes toward these advances have lagged behind. Methods:Consumer focus groups were held to explore attitudes toward genetic advances and technologies for hearing loss, views about newborn hearing screening, and reactions to the idea of adding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 24 publications
4
50
0
Order By: Relevance
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…In addition, many Deaf and hard-of-hearing individuals report an enhanced sense of self-understanding and self-identity, as well as an enhanced cultural and group identity, as a result of genetic testing. 72,85 Providing genetic services in a linguistically and culturally sensitive manner has been shown to improve outcomes such as genetics knowledge and understanding. 86,87 Furthermore, using neutral or balanced terminology, such as "chance" instead of "risk, " "deaf " or "hearing" instead of "affected" or "unaffected, " and exercising caution in the use of terms such as "handicapped, " "pathology, " and "impairment" can enhance the provision of genetic services to deaf and hard-of-hearing individuals and their families.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…For Deaf or hard of hearing individuals, undergoing genetic testing to determine whether their deafness is genetic may be used for themselves or family members to assist with their health care or with family planning issues (Arnos 2003). According to a study by Burton et al (2006), Deaf adults expressed a positive motivation to seek genetic testing to clarify their own selfidentity and to prepare for future children. As well, parents of deaf children may avail of the results of a positive genetic test for deafness as it provides accurate information about the cause of deafness and about other medical implications, as well as providing an estimate of the chance of reoccurrence in other children (Palmer et al 2009).…”
Section: Benefits Of Genetic Testing For Deaf and Hard Of Hearing Indmentioning
confidence: 99%
“…However, there was little interest in using genetic information for partner selection, making decisions whether or not to have children, with the exception of those affiliated with the Deaf communities who wanted to learn if they could have deaf children. Burton et al (2006) has also published a study that found positive attitudes towards genetic testing within the Deaf community.…”
Section: Attitudes Of D/deaf and Hard Of Hearing Individuals Towards mentioning
confidence: 99%
“…Previously, studies were mostly focused on the causes of HI (Gray 1989;Marazita et al 1993;Derekoy 2000), attitudes to prenatal diagnosis for HI (Middleton et al 1998;Brunger et al 2000;Burton et al 2006;Boudreault et al 2010;Baldwin et al 2012;Nahar et al 2013), the impact of genetic testing on the beliefs and attitudes of parents of deaf children towards genetic testing (Palmer et al 2009), and the effect of pre-test genetic counseling of deaf individuals on knowledge of genetic testing (Baldwin et al 2012). It is known that 90-95% of deaf children are born to hearing parents (Schein and Delk 1974;Mitchel and Karchmer 2004).…”
Section: Introductionmentioning
confidence: 99%